Strategic Decision-Making in Small and Medium Enterprises: A Qualitative Case Study Approach - Fahrul ulum; Husain Aziz (HARAMAIN: Jurnal Manajemen Bisnis, 2025)
Strategic decision-making plays a critical role in determining the sustainability and competitiveness of small and medium enterprises (SMEs), particularly in dynamic urban economic environments. SMEs often face challenges such as limited resources, market uncertainty, and intense competition, which require entrepreneurs to make adaptive and effective strategic decisions. This study aims to explore the strategic decision-making processes among SMEs in Bandung City, Indonesia. The research employed a qualitative case study approach to gain an in-depth understanding of how SME owners interpret business challenges, evaluate opportunities, and formulate strategic responses. Data were collected through in-depth interviews with SME owners and managers, supported by field observations and documentation analysis. The collected data were analyzed using an interactive qualitative analysis model consisting of data condensation, data display, and conclusion drawing. The findings reveal that strategic decision-making in SMEs is strongly influenced by entrepreneurial experience, market feedback, and environmental dynamics. SME owners tend to rely on experiential knowledge, customer responses, and informal discussions when determining business strategies. In addition, digital platforms such as social media and online marketplaces have become increasingly important in shaping strategic decisions related to marketing and business expansion. The study contributes to the strategic management literature by highlighting the contextual and adaptive nature of decision-making processes in SMEs. Practically, the findings provide insights for policymakers and business development institutions in designing programs that strengthen the strategic capabilities of SME entrepreneurs and support sustainable business growth.